THE PSYCHOLOGICAL NATURE AND FACTORS OF BULLYING - Asatiani , Nata; Tsereteli , Mzia (Georgian Psychological Journal, 2022)
Bullying is a growing problem all over the world. It is encountered everywhere and for this very reason it has become a major challenge of the 21ﬆ century to ﬆudy the psychological nature of bullying and analyze the factors responsible for bullying among the adolescent population. The purpose of the given desk research is to ﬆudy the psychological mechanism of bullying and identify the factors preventing bullying behavior. The corresponding sources made it possible to view bullying as an integrated syﬆem and ﬆudy its underlying psychological mechanism: the components of the syﬆem, the key factors of bullying and their interaction. The research showed signiﬁcant relationship between the following three factors: personal aggression, the exiﬆence of an object of aggression and environmental possibilities. Due to this the psychological phenomenon of bullying is viewed in the context of Anthropic Theory of Set. According to this theory, aggression, the object of aggression (victim) and the environ- ment allowing the person to manifeﬆ aggression are the necessary preconditions of bullying. The given work attempts to conﬆruct a model of bullying based on the Theory of Set, a model that represents a single syﬆem comprising various factors. The article also makes suggeﬆions regarding the further research into the operation of the syﬆem in queﬆion.